Impact of Banking Supervision on Liquidity Risk and Credit Risk: Evidence from Nigeria - Bahago, Kashema; Jelilov, Gylych; Celik, Bilal (International Journal of Economics and Financial Issues, 2019)
This study investigates the effect of banking supervision on liquidity risk and credit risk in Nigeria. This research aims to determine the extent to which liquidity and credit risk has on banking supervision as well as to investigate the interdependence of liquidity risk, credit risk and banking supervision on themselves. It is also imperative to state that a study of this nature provides an independent platform through which the regulators can appraise fundamental tools for supervision in a bid to make reasonable adjustment where necessary. This study deployed the unit root test, VAR (vector autoregressive model), the system equation for P-value, and the autocorrelation test for its analysis. The data used in this thesis is a time series data from the National Deposit Insurance Corporation (NDIC) from the year 2007 to 2017. The implication of this study will be of great benefit not only to the Nigerian banking industry and related institution but also to the public and the economy as a whole. The result (findings) showed that banking supervision does have an impact liquidity risk as “liquidity risk in both periods 1 and 2 have a positive coefficient of 0.042402 and 0.004716 respectively has a positive relationship with banking supervision”. This research found that banking supervision has a positive impact on credit risk in the Nigerian economy. But at certain time periods they will be initially negative, thereby taking some time to make impact in the economy, as this is based on policy lag, as “credit risk in period 1 has a coefficient of 1.65 and a coefficient of -5.73 at period 2 which means a positive relationship with banking supervision and a negative relationship with banking supervision respectively. My recommend is that financial institutions should adhere to the rules and regulations guiding the banking industry, as lack of adherence can lead to bankruptcy or losing the banking license, and the central bank should ensure proper enforcement of the banking laws set by the banking regulators and the banking supervisors should abide by the laws strictly devoid of corrupt practices. Keywords: Banking, Central Bank, bank supervision, credit risk JEL Classifications: G38, G10, G23 DOI: https://doi.org/10.32479/ijefi.8073